An energy-utilization metric for heat transfer devices. (December 2021) - Boraey, Mohammed A.
Abstract: A new metric for measuring the performance of heat transfer devices, which require the consumption of mechanical power to function, is proposed. The proposed Energy-Utilization Metric, EUM, is derived to quantify the achieved heat transfer rate per unit consumed mechanical power. By virtue of its definition, using the EUM as a preference metric between different heat transfer devices guarantees the selection of the design with the best energy-utilization characteristics or in other words the device which meets the required heat load with the minimum amount of consumed pumping power. The proposed metric allows an easy approach for the systematic analysis of different design parameters and their effect on the power consumption potential of heat transfer devices. The validity of the proposed EUM is confirmed using experimental and numerical data from literature. The R e number of the tested cases ranges from 2, 000 to 40, 000 with EUM ranging from 1 to 7, 700 showing the huge difference in the energy consumption potential for different designs and operation conditions. The cubic dependence of the EUM on the R e number is also confirmed using results from the literature. This strong dependence favors the operation at lower R e numbers if energy consumption is the major concern. Highlights: An Energy-Utilization Metric (EUM) is proposed as a preference criterion for heat transfer devices. The EUM represents the rate of heat transfer per unit consumed power. The EUM offers many advantages over other measures of performance. The EUM guarantees the best use of the consumed mechanical power. The EUM is validated using published experimental and numerical results.